2017
DOI: 10.1055/s-0037-1603673
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Osteochondritis Dissecans of the Lateral Femoral Condyle Combined with Discoid Meniscus

Abstract: The discoid meniscus is a rare anomaly of the knee that affects mostly the lateral meniscus and is often asymptomatic. The osteochondritis dissecans is a disorder of the subchondral bone and articular cartilage and occurs frequently associated with the discoid lateral meniscus. In the present case, we showed the evolution of this association related to surgical treatment. A patient with lateral knee pain and a magnetic resonance depicting a torn discoid lateral meniscus and osteochondritis dissecans of the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Of lateral femoral condyle lesions, 33% were seen with a discoid meniscus in the affected compartment, an association described in the literature that may require concurrent or secondary arthroscopic treatment. 9,23,45 The need for realignment procedures in this population was consistent with a significant association demonstrated between mechanical axis deviation and osteochondral defect presence in the affected compartment. 28 Malalignment has been demonstrated as a risk factor for graft failure.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Of lateral femoral condyle lesions, 33% were seen with a discoid meniscus in the affected compartment, an association described in the literature that may require concurrent or secondary arthroscopic treatment. 9,23,45 The need for realignment procedures in this population was consistent with a significant association demonstrated between mechanical axis deviation and osteochondral defect presence in the affected compartment. 28 Malalignment has been demonstrated as a risk factor for graft failure.…”
Section: Discussionsupporting
confidence: 81%
“…Of lateral femoral condyle lesions, 33% were seen with a discoid meniscus in the affected compartment, an association described in the literature that may require concurrent or secondary arthroscopic treatment. 9 , 23 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They emphasized that meniscal stabilization was effective in the treatment of OCD. Bulgheroni et al reported a case of OCD development after re-tear of DLM [ 17 ]. They mentioned the importance of preserving the peripheral meniscal rim.…”
Section: Clinical Discussionmentioning
confidence: 99%